KINERJA KEUANGAN LEMBAGA KEUANGAN MIKRO SEBELUM DAN SETELAH PELATIHAN MANAJER KE JAWA TENGAH (STUDI PADA LEMBAGA KEUANGAN MIKRO DI BANDA ACEH) - Usman Bakar (Program Magister Akuntansi Unsyiah, 2009)
The objectives of this research are to analyze: the financial performance diffirence between manager after training and manager efore training. This research was done at the Micro Finanace Institution in Aceh by using explanatory survey method. Sample unit are 29 Micro Finanace Institution. The analysis methods that is used are the difference test for unpaired two samples for means. The difference test is used to analyze the financial performance deffirence manager after training and manager before training. The hypothesis testing result shows that the financial performance of Micro Finanace Institution that manager after training is higher the financial performance of Micro Finanace Institution that manager before training at Aceh. Key words: Training Manager and financial performance